2020
DOI: 10.26452/ijrps.v11i2.2290
|View full text |Cite
|
Sign up to set email alerts
|

To study the effect of oral vitamin D supplements on wound healing in patient with diabetic foot ulcer and its effect on lipid metabolism

Abstract: To Critically Assess the effect of oral vitamin D supplements on wound healing in a patient with diabetic foot ulcer and its impact on lipid metabolism. This is a single-Centre prospective randomised, control-controlled study was conducted in Department of Surgery Datta Meghe Medical College, Hingna, Nagpur, in collaboration with Datta Meghe Institute of Medical Sciences (DMIMS) Deemed to be University from June 2019 TO March 2020. A total of sixty patients were included in this study. A randomised grouping wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…A total of 37 articles were retrieved after a systematic literature search. Nine were RCTs (13,(16)(17)(18)(19)(20)(21)(22)(23), and 28 were observational studies (15, 24-50) (12 cross-sectional, seven cohort, and nine casecontrol studies).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A total of 37 articles were retrieved after a systematic literature search. Nine were RCTs (13,(16)(17)(18)(19)(20)(21)(22)(23), and 28 were observational studies (15, 24-50) (12 cross-sectional, seven cohort, and nine casecontrol studies).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nine studies were randomised controlled trials [17][18][19][20][21][22][23][24][25]. There were two case control studies [26,27].…”
Section: Included Studiesmentioning
confidence: 99%
“…Six studies were reported from Iran [17,[19][20][21]24,25] all by the same group. Two studies were carried out in India [12,18], two in the USA [22,28], and one in each of the following; Australia [29], Bahrain [30], Nigeria [26], Saudi Arabia [27], and Sweden [23]. Data are presented as mean ± standard deviation, with decimals rounded to 1 place.…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations